2001
DOI: 10.1111/j.1527-3466.2001.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Actions of Berberine

Abstract: Berberine, is an alkaloid from Hydrastis canadensis L., Chinese herb Huanglian, and many other plants. It is widely used in traditional Chinese medicine as an antimicrobial in the treatment of dysentery and infectious diarrhea. This manuscript describes cardiovascular effects of berberine and its derivatives, tetrahydroberberine and 8-oxoberberine. Berberine has positive inotropic, negative chronotropic, antiarrhythmic, and vasodilator properties. Both derivatives of berberine have antiarrhythmic activity. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
126
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(131 citation statements)
references
References 29 publications
(56 reference statements)
1
126
0
3
Order By: Relevance
“…We pharmacologically upregulated Fbxo32 using Berberine, which is derived from the plant Hydrastis canadensis L. 26,27 Application of Berberine to Ad-shPak1-phenylephrine-NRCMs upregulated Fbxo32 expression to similar levels when compared with Ad-shC2-phenylephrine-NRCMs; this resulted in PP2B downregulation ( Figure 6A). These results indicate that Berberine does not act through Pak1.…”
Section: Treatment Potential Of Fbxo32 Induction In Ameliorating Pak1mentioning
confidence: 99%
“…We pharmacologically upregulated Fbxo32 using Berberine, which is derived from the plant Hydrastis canadensis L. 26,27 Application of Berberine to Ad-shPak1-phenylephrine-NRCMs upregulated Fbxo32 expression to similar levels when compared with Ad-shC2-phenylephrine-NRCMs; this resulted in PP2B downregulation ( Figure 6A). These results indicate that Berberine does not act through Pak1.…”
Section: Treatment Potential Of Fbxo32 Induction In Ameliorating Pak1mentioning
confidence: 99%
“…Its chemical structure is 5,8-dihydro-9,10-dimethoxy-6H-benzo(g)-1,3-benzodioxolo(5,6-a)quinolizine. Berberine exhibits a wide variety of bioactivities such as antidiarrheic (Sack and Froehlich, 1982;Taylor and Greenough, 1989), antimicrobial (Yan et al, 2008), hypolipidemic (Kong et al, 2004;Doggrell, 2005;Brusq et al, 2006;Cicero et al, 2007), hypoglycemic (Yin et al, 2002;Pan et al, 2003;Zhou et al, 2007;Turner et al, 2008;Yin et al, 2008), antiarrhythmic (Wang et al, 1994;Lau et al, 2001), anticancer (Inoue et al, 2005;Lanvers-Kaminsky et al, 2006;Lin et al, 2006Lin et al, , 2007Piyanuch et al, 2007;Serafim et al, 2008;Yu et al, 2007), anti-inflammatory (Kuo et al, 2004Lee et al, 2007), antiviral (Hayashi et al, 2007), antidepressant (Kulkarni and Dhir, 2007), and hepatoprotective (Zhang et al, 2008) effects. Its chloride salt has been used for several decades in clinical situations to treat gastroenteritis and secretory diarrhea in China.…”
Section: Introductionmentioning
confidence: 99%
“…Berberine (BBR) is a naturally occurring structurally characterized compound present in many herbs and has a variety of pharmacological properties including glucose lowering (9,15,41) and antimicrobial activities (17). We and others (9,19,38) have reported that BBR reduces body weight, causes a significant improvement in glucose tolerance, and improves insulin action in obese and/or diabetic subjects by activating AMPK.…”
mentioning
confidence: 99%